Effects of Biological Characteristics and Environmental Factors on Swimming Performance of Endemic Fish in Southwest China - Jianing Rao; Zhiguang Zhang; Yuanming Wang; Qi Wei; Guoqing Chen; Xintong Li; Ruifeng Liang; Kefeng Li (Animals)
Swimming is crucial to fish survival and reproduction, and is usually influenced by species, morphology, habitat environment and physiological condition. Understanding the changes in fish swimming ability and identifying the driving factors behind these changes is vital. In this study, seven endemic fish species from the Qingshui River, an important tributary of the upper Pearl River in Southwest China, were used to explore the effects of biological and environmental factors on fish swimming ability. The results indicated that the body length parameters had a minimal effect on the induced swimming speed (Uind) but played a positive role in critical and burst swimming ability (Ucrit and Uburst). Weight (W) and W/SL (the ratio of weight to standard body length) correlated more highly with swimming ability than body length parameters. Fish preferring the lotic environment exhibited higher Ucrit and Uburst, and fish with a streamlined morphology had a smaller Uind. The Uind, Uind/SL, Uind/W and Uind/(W/SL) of Discogobio yunnanensis (Regan, 1907) and Pseudocrossocheilus tridentis (Cui & Chu, 1986) were significantly higher during the spawning period. Acrossocheilus yunnanensis (Regan, 1904) performed better during the spawning period in Ucrit and Ucrit/SL. The Uburst of fish during the spawning period was smaller than that during the non-spawning period. Generally, the species difference had the greatest contribution to the swimming ability difference, followed by environmental conditions and fish morphology.